2010
DOI: 10.1517/14656566.2010.512288
|View full text |Cite
|
Sign up to set email alerts
|

Treating gestational trophoblastic disease

Abstract: GTN is highly responsive to chemotherapy. However, surgery is an important adjunct in select cases. Even in advanced-stage or recurrent disease, cure can be achieved and fertility preserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…In our institution, some surgical interventions are used to control complications such as hysterectomy for bleeding complication and some surgical interventions are used to remove the resistant foci. The reason for surgical intervention in this study is correlated to previous reviews (Lurain et al, 1995;Patel et al, 2010;Rodriguez et al, 2010). Multimodality treatment can improve overall survival of resistant GTN patients (Lurain, 2011;Osborne et al, 2012).…”
Section: Discussionsupporting
confidence: 81%
“…In our institution, some surgical interventions are used to control complications such as hysterectomy for bleeding complication and some surgical interventions are used to remove the resistant foci. The reason for surgical intervention in this study is correlated to previous reviews (Lurain et al, 1995;Patel et al, 2010;Rodriguez et al, 2010). Multimodality treatment can improve overall survival of resistant GTN patients (Lurain, 2011;Osborne et al, 2012).…”
Section: Discussionsupporting
confidence: 81%
“…The high cure rate after hysterectomy in our LR non-metastatic group may be attributed to the prophylactic use of 1-2 courses of MTX/FA with hysterectomy in most participating centres in this study. Rodriguez et al also supported this concept [23]. The role of hysterectomy in the LR metastatic group is less clear; Eysbouts et al reported that no cases with metastatic GTN achieved remission with hysterectomy alone [24].…”
Section: Discussionmentioning
confidence: 97%
“…In addition, Fleming et al found that patients who survived after thoracotomy for GTN were likely to have: A) perioperative hCG less than 1500 mIU/mL; B) stage III disease (no liver or brain metastases); and C) solitary pulmonary nodule [22]. Several investigators have reported that the achievement of non-detectable hCG within 1-2 weeks after resection of a solitary pulmonary nodule is highly predictive of favorable outcome [2,19]. Cao et al reported that the patients with chemotherapy-resistant GTN who received more than four regimens or 13 cycles of pre-operative chemotherapy had a poor prognosis and were less likely to benefit from pulmonary lobectomy [26].…”
Section: Surgical Managementmentioning
confidence: 99%
“…Patients with GTN are classified as having low-risk or high-risk disease using the modified World Health Organization prognostic scoring system, that is adapted by the International Federation of Gynecology and Obstetrics (FIGO). High-risk is defined by FIGO stage IV or any FIGO stage with a score ≥7, which indicates multi-agent chemotherapies as standard therapy [2,3].…”
Section: Introductionmentioning
confidence: 99%